2020
DOI: 10.5588/ijtld.19.0163
|View full text |Cite
|
Sign up to set email alerts
|

National population-based tuberculosis prevalence survey in Ghana, 2013

Abstract: BACKGROUND: The prevalence of tuberculosis (TB) disease is one of the three main indicators used to assess the epidemiological burden of TB and the impact change of TB control; the other two are incidence and mortality.OBJECTIVE: To estimate the prevalence of TB disease among adults in Ghana.METHODS: A nationally representative cross-sectional survey was conducted. Participants were screened for TB using interview and chest X-ray (CXR). For those participants with cough ≥2 weeks and/or abnormal CXR, spot and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In general males are more at risk for TB in Ghana and other countries and our study findings are in line with this [22,29]. It is reported that in illegal artisanal small-scale mining settings in Ghana, women may constitute up to 50% of the labour force and play various roles [16,30,31].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In general males are more at risk for TB in Ghana and other countries and our study findings are in line with this [22,29]. It is reported that in illegal artisanal small-scale mining settings in Ghana, women may constitute up to 50% of the labour force and play various roles [16,30,31].…”
Section: Plos Onesupporting
confidence: 89%
“…In case, a significant proportion of those missed were miners, given the higher risk of TB among miners, it could be possible that our results may be an underestimation of the TB burden in AMC studied [18]. The prevalence of TB among the people screened in the artisanal mining communities in this study was more than two and half times what was reported for the general population in Ghana in the TB prevalence survey (356 bacteriologically confirmed TB per 100,000), on the face value re-iterating the data on the higher risk of TB among mining communities [9,18,22].…”
Section: Plos Onementioning
confidence: 64%
“…Male sex, marriage, at least primary education, employment, a good knowledge and practice of TB were predictive of more favourable attitudes to TB. However, the association of male sex with a positive attitude towards TB is unexpected given the Gambian TB prevalence survey [ 3 ] just like others [ 4 , 43 , 44 ] and in concordance with global TB epidemiology shows majority of TB cases are males [ 1 ]. This may be closely related to their health-seeking behaviour when they have TB-like symptoms [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disparity between health seeking behaviour and case detection in the community underlies the importance of ensuring health centres are adequately equipped, and health workers are adequately trained to, facilitate early diagnosis and treatment of TB. These will help prevent missed opportunities for TB diagnosis and reduce the spread of TB and possibly associated stigma [ 1 , 18 , 38 , 44 , 45 ]. It is possible that reported health-seeking behaviours might be different from actual actions which may also explain the discordance between a favourable attitude to TB and the preponderance of undiagnosed male TB cases during the TB prevalence survey in Gambia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes, smoking) or bovine TB were excluded. Of 162 published papers, only seven were of relevance [18–24]. Grey literature, such as unpublished survey reports produced by national TB programmes, abstracts and presentations from international meetings, and routine progress updates collated by the WHO Global Task Force on TB Impact Measurement on the status of surveys since 2008, was also systematically reviewed [25–36].…”
Section: Methodsmentioning
confidence: 99%